Interoperability criteria, mechanisms, and evaluation of system performance for transparently interoperating WLAN and UMTS-HSDPA networks. - Al-Gizawi, T.
The main challenge in the development of future wireless communication systems is to provide users with a wide range of services across different radio access technologies through a single mobile terminal, while maintaining the minimum QoS requirements, and ideally with no limits on the coverage area, mobility or radio conditions. Thus, the need for seamless interworking between heterogeneous wireless communication systems consisting of multiple radio access technologies and overlapping networks emerges. In this article we address the main issues that arise while implementing the interoperability mechanisms between two different radio access networks, with emphasis on UMTS-HSDPA and WLAN (HIPERLAN/2). Two interoperability mechanisms are introduced and described in detail: initial user assignment (optimal network selection) and intersystem handover. Both mechanisms are activated via the optimization of a suitably defined cost function which takes into account all the appropriate system level parameters that trigger the interoperability process. Finally, we investigate the overall performance of the proposed mechanisms by means of a software simulation platform. A number of simulations have been carried out in order to demonstrate the performance enhancements achieved by the proposed mechanisms in terms of unsatisfied users, dropped handovers, and system throughput.
Keywords: HIPERLAN/2.; UMTS; Universal Mobile Telecommunications System; WLAN; Dropped handovers; Heterogeneous wireless communication systems; High speed downlink packet access; Initial user assignment; Interoperability mechanisms; Intersystem handover; Multiple radio access technologies; Optical network selection; Overlapping networks; Radio access networks; Single mobile terminal; Unsatisfied users; Wireless local area networks